2017
DOI: 10.12681/bgsg.11130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative geochemistry of three urban streams in Athens: Kifissos-Podoniftis-Pikrodafni

Abstract: The geochemistry of three urban streams in Athens was analysed and compared on the basis of major elements and heavy metals content in water and active sediment. The studied streams of Kifissos, Podoniftis and Pikrodafni run through the Athens basin of a total area of 540 km2 but differ with respect to the origin of their headwaters i.e., Parnitha, Penteli and Hymettus mountains. The main aim of the study was to determine the geochemical signature of water and sediment within the Athens hydrological basin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Even the upstream station (K MD) illustrated a poor or bad physicochemical water quality status in more than 50% of the sampling efforts. An existing study [28] for the Kifisos river revealed similar influence by anthropogenic activities regarding major elements (nitrate and phosphate concentrations). Another study [29] revealed that the Kifisos river is highly polluted and ranked the river's quality as very poor regarding species diversity.…”
Section: Discussionmentioning
confidence: 78%
“…Even the upstream station (K MD) illustrated a poor or bad physicochemical water quality status in more than 50% of the sampling efforts. An existing study [28] for the Kifisos river revealed similar influence by anthropogenic activities regarding major elements (nitrate and phosphate concentrations). Another study [29] revealed that the Kifisos river is highly polluted and ranked the river's quality as very poor regarding species diversity.…”
Section: Discussionmentioning
confidence: 78%
“…In Greece, urban flooding is probably the most frequent type of flood hazard, while some of the most catastrophic events have occurred in the Athens metropolitan area (Koutsoyiannis et al 2012). The streams of Attica, despite the fact that almost 90% of them have been covered (Hadjibiros 2014) and most are also suffering from environmental degradation due to anthropogenic activities (Argyraki et al 2013) through rapid and violent urbanization, are also often responsible for flash flood events, endangering the residences in the riparian zone and often causing severe damage and human casualties. The gentle slope morphology, the special climatological conditions, the uncontrolled urbanization without the necessary concurrent infrastructural work and the lack of adequate green spaces that would allow sufficient infiltration of precipitation, are the main causes of the increased flood risk of the area (Dimitriou et al 2012, Lasda et al 2010.…”
Section: Introductionmentioning
confidence: 99%